Production and productivity of 1,3-propanediol from glycerol by Klebsiella pneumoniae GLC29 - Da Silva, Gervásio Paulo (2015)
Interest in the development of the bioproduction of 1,3-propanediol, an important chemical intermediate with various industrial applications, has increased in recent years. Klebsiella pneumoniae is one of the most studied and efficient bacteria for 1,3-propanediol production from glycerol. A new isolate of K. pneumoniae was investigated using response surface methodology by central composite design for the production of 1,3-propanediol using glycerol. The effects of pH, temperature, stirrer speed, and glycerol concentration on the production and productivity of 1,3-propanediol were examined. Considering both production and productivity, the best conditions for glycerol conversion in 1,3-propanediol are: a pH range of 6.9-7.1, a temperature between 33 and 38.5°C, a stirrer speed of 110-180 rpm, and a glycerol concentration of 39-49 g l-1. Batch fermentation carried out at a pH of 7.0, a temperature of 35°C, a stirrer speed of 150 rpm, and a glycerol concentration of 40 g l-1 produced 20.4 g 1,3-propanediol l-1, with a maximum volumetric productivity of 2.92 g l-1 h-1 and a yield of 0.51 g g-1. The main byproducts were acetic acid (approximately 7.0 g l-1) and formate (approximately 3.7 g l-1). The newly isolated K. pneumoniae GLC29 showed potential for the conversion of glycerol into 1,3-propanediol, with high production and productivity.